EXPLORING THE FIRST APPEARANCE OF THE MAIN DERIVED CONIFER FAMILIES OF GONDWANA: EVIDENCE PROVIDED BY THE TRIASSIC WOODS FROM ARGENTINA (Ameghiniana, 2023)
The relevance of improving the knowledge on Triassic conifers resides in that the modern clades originated during the Late Triassic–Early Jurassic. More than 30 conifer-like fossil woods are known from the Triassic strata of Argentina. Whereas some have not been linked to any family, others have been related to the “Protopinaceae”, Taxaceae, Podocarpaceae, Araucariaceae, Cupressaceae, or Hirmeriellaceae (=Cheirolepidiaceae). The diversity of woods with anatomy close to derived conifers contrasts with the scarce Triassic record of leaves and micro and megasporangiate cones, which could be explained by a combination of taphonomic and evolutionary causes. In order to provide information to resolve this controversy, the anatomy and systematic affinities of Triassic permineralized conifer-like trunks and woods described to date for Argentina were reassessed. As a result of this review, it emerged that the woods previously assigned to Podocarpaceae and Taxaceae do not have enough preserved characters to support such assignment, or they have characters that are homoplasic in the context of Mesozoic gymnosperms and therefore their affinity is ambiguous. On the contrary, the reevaluation of the woods related to the Araucariaceae, Cupressaceae and Hirmeriellaceae (=Cheirolepidiaceae) allows us to support their affinity with these families.